Nurse performance and the knock out polio 1997 in a Metro Manila health district - Sandalo, Maribel R.
The community health nurse's primary obligation is to provide health services to the populace. Her work deals with providing holistic and continuing health care that focuses on early diagnosis and treatment directed towards fostering a sense of responsibility among the people of the community.The community health nurse works closely with the physician. She acts as a manager, supervisor and coordinator to other health team members. This is probably the reason why she was given the task to lead the Department of Health's National Immunization Day/Knock Out Polio (NID/KOP) implementation from the preparatory, actual and evaluation phases. Considering other tasks and activities the community health nurse is expected to render at the health center, the nurse is burdened with the fact that the success of the immunization program depends on how she performs her role as its manager and supervisor.This study investigates if the success of the Knock Out Polio (KOP) is related to nurse performance. It also describes performance and extent of participation of the nurse in KOP activities. The study likewise investigates whether the factors related to KOP activities (manpower, support system, logistics and supplies and OPV posts) will enhance nurse performance resulting in high KOP coverage outcome.The study was conducted in the three (3) cities of District Health Office (DHO) IV (Las Pi?as, Muntinlupa and Para?aque). Fifty two (52) community health nurses assigned to the health centers of the aforementioned cities were the subjects of the study. They were observed during the three (3) phases of KOP activities - preparatory, actual and evaluation phases. Statistical treatment of the data utilized descriptive statistics, Pearson product moment correlation coefficient; ANOVA and T-test with the level of significance preset at =.05.The study yielded these major findings:1) The community health nurses' mean level of performance in carrying out each of the functions during KOP was interpreted to be outstanding. In all phases, nurse's performance rating was outstanding, but the nurses obtained highest performance during the actual and evaluation phases.2) There were only nine (9) health centers with high KOP coverage outcome. This can be attributed to the following factors: (a) saturation of small population size of the communities covered by the health centers; (b) presence of mobile health teams; and (c) presence of Oral Polio Vaccine (OPV) posts in accessible areas. On the other hand majority (83) of the health centers reported low coverage outcome due to the following reasons: (a) a number of health centers cover elite subdivisions; (b) some of the health centers are physically inaccessible; (c) inappropraite scheduling of immunization days; (d) lack of transportation allowance among health care workers in order to reach far-flung areas; and (e) high degree of saturation of target population since KOP is on its 4th year of implementation.3) The data did not show any significant relationship between nurse performance and KOP coverage outcome (p value = 0.204).